2005
DOI: 10.1016/j.heares.2005.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Damage and threshold shift resulting from cochlear exposure to Paraquat-generated superoxide

Abstract: Superoxide has been implicated as a contributing factor to cochlear pathology from a number of sources, including noise and ototoxic drugs. The effects of NADPH oxidase-dependent superoxide on the cochlea were investigated in the current study using paraquat (PQ). PQ is a toxic herbicide that causes tissue damage by generating superoxide through reduction of molecular oxygen in a reaction catalyzed by NADPH oxidase. The current study examined the effects of round window PQ administration on inferior colliculus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 44 publications
1
35
0
4
Order By: Relevance
“…Interestingly, there are growing data indicating the association between chronic Paraquat exposure and Parkinson's disease [20][21][22]. The mechanism of viologen toxicity involves the induction of the generation of superoxide anions and other ROS, which leads to cell and tissue damage [23,24]. Recent studies have shown that incorporating viologen units into the dendritic backbone can yield new positive biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there are growing data indicating the association between chronic Paraquat exposure and Parkinson's disease [20][21][22]. The mechanism of viologen toxicity involves the induction of the generation of superoxide anions and other ROS, which leads to cell and tissue damage [23,24]. Recent studies have shown that incorporating viologen units into the dendritic backbone can yield new positive biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst treatments exist for middle ear conditions, there are virtually no treatments that can ameliorate the damage to the inner ear and reduce the impact of sensorineural hearing loss. There is increasing evidence that oxidative stress and the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS) are key elements in the pathogenesis of cochlear injury due to noise exposure [3][4][5][6][7]. Compounds that target the mechanisms underlying oxidative stress thus offer considerable potential as therapies for hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies by Bielefeld E C et al (2005) and Harris K C et al (2006) showed shifting of evoked potential threshold and loss of inner and outer hair cells following application of 10mM, 5mM and 3mM of PQ to cochlea through a surgical incision (33,34). The current study did not look into the auditory threshold level.…”
Section: ++mentioning
confidence: 54%